The Effects Of Teachers' Attitudes On Students' Personality And Performance - Uluğ, Mücella; Eryılmaz, Ahu; YILDIRIM, MELİS SERAY ÖZDEN (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2011)
The emphasize of student centered educational topics is usually on the effect of teachers' attitudes on students' academical success with a lack of lifespan developmental perspective. A teacher with his teaching methods and furthermore with his attitudes and behaviours, provides his students to gain a mentally healthy personality and to have a new clear world view by leaving unforgettable traces on them. This is a prepatory study to uncover how attitudes of teachers affect the personalities and performances of students. In this sense this study will provide an emic understanding of education and the dynamics of relationship between teachers and students beyond the limited areas of classes and courses. Sample group of research consists of totally 353 students from different departments of Istanbul Kultur University and Maltepe University. By giving a questionaire the students were asked to give samples of their primary school, secondary school, high school and university teachers' positive and negative attitudes and behaviours as well as to tell how it effects their personality development and performances by giving samples. The most important findings of the research evidenced that teachers' positive attitudes have positively influence students' personality as well as their life performances. Based on these findings teachers' role in lifespan education as beyond a simple knowledge transformation is discussed. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the 2nd World Conference on Psychology, Counselling and Guidance.
Keywords: teachers' attitudes; students' personality; students' performance; öğretmenlerin tutumları; öğrencilerin kişilik; öğrencilerin performansı